From Africa to Antarctica: Exploring the Metabolism of Fish Heart Mitochondria Across a Wide Thermal Range - Hunter-Manseau, Florence; Desrosiers, Véronique; Le François, Nathalie R.; Dufresne, France; Detrich, H. William; Nozais, Christian; Blier, Pierre U. (Frontiers in Physiology, 2019)
The thermal sensitivity of ectotherms is largely dictated by the impact of temperature on cellular bioenergetics, particularly on mitochondrial functions. As the thermal sensitivity of bioenergetic pathways depends on the structural and kinetic properties of its component enzymes, optimization of their collective function to different thermal niches is expected to have occurred through selection. In the present study, we sought to characterize mitochondrial phenotypic adjustments to thermal niches in eight ray-finned fish species occupying a wide range of thermal habitats by comparing the activities of key mitochondrial enzymes in their hearts. We measured four enzymes that control substrate entrance into the tricarboxylic acid cycle: pyruvate kinase (PK), pyruvate dehydrogenase complex (PDHc), carnitine palmitoyltransferase (CPT), and hydroxyacyl-CoA dehydrogenase (HOAD). We also analyzed enzymes of the electron transport system (ETS): complexes I, II, I+III and IV. Enzymes were assayed at five temperatures (5, 10, 15, 20, and 25 °C). Our results showed that the activity of CPT, a gatekeeper of the fatty acid pathway, was higher in the cold-water fish than in the warmer-adapted fish relative to the ETS (complexes I and III) when measured at the species optimal temperatures. The activity of HOAD showed a similar pattern relative to CI+III and thermal environment. By contrast, PDHc and PK did not show the similar patterns with respect to CI+III and temperature. Cold-adapted species had high CIV activities compared to those of upstream complexes (I, II, I+III) whereas the converse was true for warm-adapted species. Our findings reveal a significant variability of heart mitochondrial organization among species that can be linked to temperature adaptation. Cold-adapted fish do not appear to compensate for PDHc activity but likely adjust fatty acids oxidation through higher activities of CPT and HOAD relative to complexes I + III.